The role of islamic school principals to develop teacher competencies in improving the quality of learning - Ruslaini, Ruslaini; Mukhlis, Amir; Fatimah, F; Sumarno, S (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
The research aims to determine the role of Madrasah Principal in developing teachers' abilities. This research is important to carry out in order to get an overview of its role in developing teachers' abilities. The method used in this study is quantitative descriptive.  The subject of the study is the Principal of MIN 4 Banda Aceh. Collection techniques through interviews, questionnaires, observations and documentation. The data analysis technique uses percentages.  The results of the study show that the function of the Madrasah Principal as an educator creates a conducive school climate, enlightens school residents, provides encouragement to education personnel, as a manager is able to face various problems in school, thinks analytically, conceptually, and always tries to be a mediator in solving various problems. As an administrator, he is closely related to various administrative management activities that are record-keeping and documenting of all school programs. As a supervisor,  supervise the work carried out by education staff. As a leader, he provides guidance and supervision, and is able to build two-way communication in carrying out various tasks. Thus, it can be concluded that the role of the Madrasah Principal can develop teacher competence in improving the quality of learning.